Graph-Based IVUS Segmentation with Efficient Computer-Aided Refinement - Sun, Shanhui (2013)
A new graph-based approach for segmentation of luminal and external elastic lamina (EEL) surface of coronary vessels in gated 20 MHz intravascular ultrasound (IVUS) image sequences (volumes) is presented. The approach consists of a fully automated segmentation stage (‘new automated’ or NA) and a user-guided computer-aided refinement (‘new refinement’ or NR) stage. Both approaches are based on the LOGISMOS approach for simultaneous dual-surface graph-based segmentation. This combination allows the user to efficiently combine general information about IVUS image appearance and case-specific IVUS morphology and therefore deal with frequently occurring issues like calcified plaque – causing signal shadowing – and imaging artifacts. The automated segmentation stage starts with pre-segmenting the lumen to automatically define the lumen centerline, which is used to transform the segmentation task into a LOGISMOS-family graph optimization problem. Following the automated segmentation, the user can inspect the result and correct local or regional segmentation inaccuracies by (iteratively) providing approximate clues regarding the location of the desired surface locations. This expert information is utilized to modify the previously calculated cost functions, locally reoptimizing the underlying modified graph without a need to start the new optimization from scratch. Validation of our method was performed on 41 gated 20 MHz IVUS data sets for which an expert-defined independent standard was available. Resulting from the automated stage of the approach (NA), the mean and standard deviation of the RMS area errors for the luminal and external elastic lamina surfaces were 1.12 ± 0.67 mm(2) and 2.35 ± 1.61 mm(2), respectively. Following the refinement stage (NR), the RMS area errors significantly decreased to 0.82±0.44 mm(2) and 1.17±0.65 mm(2) for the same surfaces, respectively (p < 0.001 for both surfaces). The approach is delivering a previously unachievable speed of obtaining clinically relevant segmentations compared to the current approaches of automated segmentation followed by manual editing.